What is the derivative of -cosx*ln(secx+tanx)cosxln(secx+tanx)?

1 Answer
May 9, 2015

Just do the product rule, followed by the chain rule (on only the ln(u)ln(u)). Recall that d/(dx)[cosx] = -sinxddx[cosx]=sinx, and that d/(dx)[ln(u(x))] = 1/(u(x))(du(x))/(dx) = 1/(u(x))((d)/(dx)[u(x)])ddx[ln(u(x))]=1u(x)du(x)dx=1u(x)(ddx[u(x)])

So:
d/(dx)[-cosx*ln(secx+tanx)]ddx[cosxln(secx+tanx)]

= [-cosx*(1/(secx+tanx))*(secxtanx+sec^2x)]+[ln(secx+tanx)sinx]=[cosx(1secx+tanx)(secxtanx+sec2x)]+[ln(secx+tanx)sinx]

Move the cosine in:
= [(-cosx/(secx+tanx))*(secxtanx+sec^2x)]+[ln(secx+tanx)sinx]=[(cosxsecx+tanx)(secxtanx+sec2x)]+[ln(secx+tanx)sinx]

Factor and cancel:
= [(-cosx/cancel(secx+tanx))*{secx(cancel(tanx+secx))}]+[ln(secx+tanx)sinx]

Notice that secx = 1/cosx:
= [-cosx*secx]+[ln(secx+tanx)sinx]

And you get:
= -1+sinxln(secx+tanx)